Augmented reality for maritime navigation data visualisation: a systematic review, issues and perspectives. (12th September 2021) - Laera, Francesco; Fiorentino, Michele; Evangelista, Alessandro; Boccaccio, Antonio; Manghisi, Vito M.; Gabbard, Joseph; Gattullo, Michele; Uva, Antonio E.; Foglia, Mario M.
Abstract: This study investigates the use of augmented reality technology (AR) in the field of maritime navigation and how researchers and designers have addressed AR data visualisation. The paper presents a systematic review analysing the publication type, the AR device, which information elements are visualised and how, the validation method and technological readiness. Eleven AR maritime solutions identified from scientific papers are studied and discussed in relation to previous navigation tools. It is found that primitive information such as course, compass degrees, boat speed and geographic coordinates continue to be fundamental information to be represented even with AR maritime solutions.